Agri-food Value Chain Revolutions in Low- and Middle-Income Countries - Barrett, Christopher B.; Reardon, Thomas; Swinnen, Johan; Zilberman, David (Journal of Economic Literature, 2022)
Agri-food value chains (AVCs) intermediate the flow of products between largely rural farmers, fisherfolk, or herders and increasingly urban consumers. The theoretical models that historically structured research on the economic development process assumed away AVC functions, however, and AVC firms and workers were necessarily omitted from the household data that generated most empirical findings in the agricultural and development economics literatures. As a result, the discipline has somewhat overlooked the rapid growth and structural change in AVCs over the past few decades that turned AVCs into major employers and sources of value addition, as well as key loci for technology transfer and foreign investment. This paper offers an integrated, structured, empirical narrative of how and why AVC revolutions occur in developing countries, the impacts of those changes, and the abundant economic research opportunities these structural changes afford economists. (JEL L14, L81, O13, O33, Q12, Q13, Q17)